POLA GAYA HIDUP DALAM KEUANGAN KELUARGA (Studi Kasus:Unit Kerja Institusi Pendidikan Swasta di Bandung) - Ridwan S. Sundjaja; Budiana Gomulia; Dharma Putra Sudjaja; Felisca Oriana S; Inge Barlian; Meilinda .; Vera Intanie Dewi (Center for Economic Studies Universitas Katolik Parahyangan, 2011)
This research was conducted to discover lifestyle patterns in family finances. This research was conducted in a private educational institution in Bandung. Data collection technique used in this research is survey technique with questionnaires and the data analysis technique that used in this study is descriptive analysis. It has been found that the lifestyle patterns of employees at one of private educational institution in Bandung generally still have a good patterns. This is proved by the monetary sequences of their revenues and expenses. Also, the priority selection of their needs and wants in fulfilling their life style is still in control. From this research, it is known generally the respondents already have their own house, vehicles, and mobile communication devices like hand phone. The purchasing frequency of hand phone in average is less than 2 times per year. Moreover, the respondents have already had a habit of saving/investing and buying insurance. To fill their spare time, respondents prefer to gather with their family, go to mall with frequency of 1-4 times per month and do exercise. But, the problem that needs to be taken care of is how to handle their credit cards/loans because a lot of respondents have routine spending of paying credit card installment/loans. From this research, it is also found that there is still a lack of awareness for making simple bookkeeping of their revenues and expenses. Therefore to make them family finances literate, they need to follow a counseling and training on family finances. Even, they are suggested to follow the counseling and training with their family members.